EFFECTS OF ACTIVITY- BASED STRATEGY ON STUDENT ATTITUDE AND ACHIEVEMENT IN CHEMISTRY IN SENIOR SECONDARY SCHOOLS, FEDERAL CAPITAL TERRITORY ABUJA, NIGERIA - Aminu, Abdulkarim; Dajal, R G; Ojelade, I A (International Journal of Allied Sciences (IJAS), 2025)
This paper was motivated by the need to determine the influence of an inquiry teaching strategy on students’ attitudes and achievement in chemistry. This study was conducted to determine the effects of Activity-Based Strategy on the Attitude and Achievement of Students in Chemistry in Senior Secondary Schools in the Federal Capital Territory, Abuja. This study employed a quasi-experimental design. Specifically, the study applied a pre-test, post-test non-randomized control group. The study population comprised all SS II Chemistry students in public senior secondary schools in the Federal Capital Territory, Abuja. The sample size of the study was 98 (SS II) chemistry students drawn through simple random sampling and purposive sampling procedures. The instruments used for data collection were Chemistry Attitude Scale (CAS) and Chemistry Achievement Test (CAT) developed by the researcher. The instruments were validated by three experts in science education. The reliability index of the Chemistry Attitude Scale was determined using Cronbach’s alpha, which gave an index of 0.72, while the Chemistry Achievement Test was also pilot tested in the same school, and the reliability index was determined using Kuder-Richardson formula (Kr-21), which gave an index of 0.81.The data obtained from the study were analyzed using mean and standard deviation to answer the research questions while the two hypotheses were tested at 0.05 level of significance using ANCOVA. The results revealed that students taught using activity-based strategy had higher mean achievement mean and attitude score than those taught using conventional chemistry methods. Hence, the activity-based strategy was found to be a facilitative instructional strategy for improving the mean achievement and attitude scores in senior secondary school chemistry. It was therefore recommended among others that chemistry teachers should be encouraged to incorporate an activity-based strategy of teaching since this method provides the opportunity to engage students in learning activities and encourages their achievement toward chemistry